MODELLING DIAMETER INCREMENT OF NATURAL FOREST STATE III IN FOUR PROVINCES IN THE CENTRAL REGION, VIETNAM - Thi Thu Hien, Cao; Thi Phuong, Luong (Journal of Forestry Science and Technology, 2018)
The data from 12 permanent sample plots (PSPs) were collected in 2005, 2012 and 2013 in four provinces Ha Tinh, Thua Thien Hue, Binh Dinh and Khanh Hoa. Each plot has an area of one ha (100 m x 100 m). All trees equal to or larger than 6 cm diameter at breast height (DBH ≥ 6 cm) were identified by species, their diameter was measured at 1.3 m. The data from 12 plots were used to model the periodic annual diameter increment for individual important tree species in each province and four important tree species which occurred in all or at least in three provinces. The response variable was the periodic annual diameter increment. The results illustrate that only one predictor, lnDBH2005, to be a significant regression model for about 47.1% to 75% important species in each province. With the remaining important species, a simple, namely constant growth model ADIk = exp(b0 + ek) was sufficient. The most frequently negative logarithmic relationship between initial diameter (DBH2005) and the periodic annual diameter increment implies that data are from stands, where the maximum growth rates occur for trees of lower diameter classes. Linear mixed effects models with plots as random effects on intercepts and slopes were chosen for the four important species S. wightianum, G. subaequelis, D. sylvatica, and N. melliferum, which occurred in at least three of the four provinces. The explained variance by the random plot effects varied from 85.09% to 90.02%.